Schottky-Barrier Photodiode Internal Quantum Efficiency Dependence on Nickel Silicide Film Thickness - Joshua Duran; Andrew Sarangan (IEEE Photonics Journal)
In this paper we show that the internal quantum efficiency of NiSi Schottky-barrier photodetectors can be significantly improved as the silicide film thickness is reduced close to its percolation threshold. We fabricated photodetectors in two optical configurations (front-side and back-side illuminated) at four different film thicknesses between 1–4 nm as well as a thick (100 nm) reference device. We simultaneously fit the reflection and transmission data for each silicide film on silicon as well as for front and backside illuminations to extract the refractive index dispersion of each film. Using this technique, we can accurately determine the absorption of each constituent layer and extract the wavelength-dependent internal quantum efficiency from the external quantum efficiency. We show that the internal quantum efficiency is highly dependent on the silicide film thickness while the dark current is not. The internal quantum efficiency of our thinnest detector is the highest reported of any silicide Schottky-barrier photodetector of comparable barrier height to date with a 57× improvement over the thick (reference) device. Using an approximation to Vickers’ model, we were able to fit the IQE spectra to extract the hot carrier mean-free path of electrons in NiSi.